Development of a Mobile Game Application to Boost Students' Motivation in Learning English Vocabulary - Elaish, M.M. (2020)
Currently, the power to master the English language has become prominent in academia, research, and business. Therefore, many non-English speaking countries, including Arab countries, are striving to improve their education systems in teaching English as a foreign language, and English vocabulary is an important factor to boost English proficiency among Arab students. Moreover, in Arab countries, there is a lack of motivation among learners of English as a foreign language which affects the learning process of students. As such, digital gaming technologies, especially mobile games, are emerging as the best way to create enthusiasm for learning new languages. Therefore, a mobile application named VocabGame was developed based on a set of persuasive guidelines, and it was launched in the Google Play Store. This paper investigated whether the developed VocabGame can motivate native Arab students learning the English language to achieve better performance. Sixty-four students were divided equally into two groups: the control group (high-performance group) and the experimental group (low-performance group). Students in the experimental group improved their motivation level significantly after the mobile learning intervention. Our findings showed that mobile game application is helpful for those students who had poor performance initially while studying English and improves their confidence. There was also an association between the pre-test and the post-test scores according to the motivation to learn based on the analysis of the covariate analysis with η-p2 being 0.148. A mobile application game was successfully developed to motivate Arab native students to learn English as a secondary language. © 2019 IEEE.